Development of Applied Linguistics - Ramonienė, Meilutė (Lietuvių kalba, 2024)
The aim of the article is to review the development of applied linguistics in Lithuania, analyse the general tendencies of the development of this science, and present the more prominent groups of researchers in applied linguistics, the schools that have been formed or are being formed, and the contribution of some researchers to the research of different branches of applied linguistics. The article focuses on the work started after the restoration of independence of the Republic of Lithuania in 1990, because only from that time onwards did the work of Lithuanian applied linguistics enter the international mainstream of this science. It discusses some of the research and practical work related to the research that helps or has helped in certain periods to solve problems related to language in life. First of all, the article introduces the works on teaching Lithuanian as a foreign language, which are connected with the beginning of applied linguistics in Lithuania, and which have laid the appropriate methodological foundations for the formation of communicative competence, for the development of a new type of textbooks, pedagogical grammars of the Lithuanian language, and for the creation of a system of assessment of competences. After discussing the origins of applied linguistics in Lithuania, the paper discusses the further development of this science. Research in the field of language acquisition, sociolinguistics, language attrition, cognitive linguistics, pragmatics, politeness and impoliteness, corpus and forensic linguistics, and other branches of applied linguistics is presented, and the real-life linguistic issues, analysed by Lithuanian researchers, are highlighted. The final section of the article describes the most important works of dissemination of applied linguistics and presents the research journal Taikomoji kalbotyra (“Applied Linguistics”), the international conferences on applied linguistics that have taken place in Lithuania, and the networks of researchers.